ANALISIS USAHA PEMASARAN IKAN HIAS TOKO BINTANG BARU AQUARIUM KOTA SAMARINDA - Dara Desi Maharani; Helminuddin; Muhammad Syafril (2339-1324, 2023)
This study aims to analyze the net profit and business feasibility of ornamental fish at the Bintang Baru Aquarium Store seen from the RCR value. The sampling technique used is purposive sampling. The results of this study indicate that the net profit received is Rp. 9,974,510/month. The profit is obtained from the difference between the total revenue (TR) of Rp. 51,074,000/month with the total cost (TC) of Rp. 41,099,490/month. The Feasibility of the Ornamental Fish Shop at Bintang Baru Aquarium seen from the value of the Revenue Cost Ratio (RCR) obtained is 1.24, which means that if there is an expenditure of Rp. 1 million will get an income of Rp. 1.24 million, meaning that the business being carried out is profitable and can be said to be feasible to be continued or developed.